Estabilidade pós-contenção das alterações da forma do arco inferior na má oclusão de Classe II de Angle tratada com e sem a extração de pré-molares - Busato, Mauro C. Agner [UNESP] (2006)
AIM: the purpose of this research was to compare the relapse of the postretention lower arch form in patients with Class II malocclusions, that were treated with either two or four premolar extraction therapies. METHODS: Group 1 consisted of 19 patients (9 male e 10 female) treated with two premolar extraction, and group 2 consisted of 47 patients (20 male e 27 female) treated with four premolar extraction. The initial mean age of the first group was 14.04 years, and the initial mean age for group two was 13.03 years. Individual variables of the mandibular arch, such as intercanine width, intermolar width and arch length, were evaluated in the pre-treatment, end of active treatment and five years posttreatment diagnostic casts of each patient. lndependent t tests were used to compare the differences of the variables between groups. RESULTS: results demonstrated that there were no statistically significant difference between the groups for posttreatment constriction of the mandibular arch (width and length). CONCLUSION: it was concluded that the treatment of Class II malocclusion with two premolar extraction provides the same stability for lower arch form as the treatment with four premolar extraction.